Defining youth-centred practice in mental health care - Alec Cook; Renee Hunt; Jennifer Silcox; Eugenia Canas; Arlene G. MacDougall (BMC Psychiatry)
Abstract Background Like many other nations, the rates of mental illness among children and youth have risen. Youth and emerging adults (YEA) between the ages of 16 and 25, in particular, have the highest rate of mental health disorders of any age group leading clinicians and researchers to ponder new and innovative ways to treat mental ill health (1–2). Youth centred practices (YCP) have emerged as possible new approaches in youth mental health care to better treat YEA living with mental illness, but also to empower this population to take control of their wellbeing. Despite the growing use of the term ‘youth-centred,’ there is little consensus on what this looks like in mental health care for youth. Using research coming out of MINDS of London-Middlesex, we explore how mental health professionals, including clinicians, researchers, administrative staff, and trainees, understand the term YCP and how they implement youth-centredness in practice. Methods Using a Youth Participatory Action Research framework as a guide, MINDS’ researchers worked alongside YEA research assistants in all phases of research. Participants were selected from a pool of known practitioners and mental health programs utilizing YCP, as identified by YEA research assistants. Qualitative focus group and interviews, developed using an appreciative inquiry approach, were conducted with 13 mental health care professionals, staff, and trainees to ascertain how they understand and practice YCP. Researchers conducted a codebook thematic analysis of the data: five themes and fourteen subthemes were identified. Results Our analysis identified five main themes: (1) Acknowledging YCP’s Role in Supporting YEA Mental Health; (2) Developing Authentic and Meaningful Relationships Between YEA and Care Providers; (3) Collaboration in Care: Engaging YEA as Active Agents in their Treatment; (4) Creation and Maintenance of Accessible Service to Facilitate YEA Engagement; and (5) Moving Beyond Tacit Knowledge to YCP as a Trainable Construct. Underlying each of these key components of YCP was a thread of recognition that systems of care for YEA must be responsive to the unique needs of those the system intends to serve. This process is seen as dynamic and fluid; often representative of societal change and growth, the specific needs of YEA will remain in flux and YCP approaches require continued reflexivity. Conclusions When YCPs are used in mental health care, YEA and their lived experiences are respected by trusted adults on their care team. At the core, YCPs are collaborative. There is a shift from the dynamic of “practitioner as expert” to one that provides YEA a sense of agency and autonomy to make informed decisions regarding their care.